2022
DOI: 10.1093/braincomms/fcac201
|View full text |Cite
|
Sign up to set email alerts
|

Development of prognostic models for survival and care status in sporadic Creutzfeldt-Jakob disease

Abstract: Sporadic Creutzfeldt-Jakob disease, the most common human prion disease, typically presents as a rapidly progressive dementia and has a highly variable prognosis. Despite this heterogeneity, clinicians need to give timely advice on likely prognosis and care needs. No prognostic models have been developed that predict survival or time to increased care status from the point of diagnosis. We aimed to develop clinically useful prognostic models with data from a large prospective observational cohort study. 537 pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In the present study, in line with recently proposed prognostic models [38,39], we carried out the survival analyses also considering clinical variables known to have a prognostic role in prion diseases such as age at LP, PRNP codon 129 genotype, and time between symptoms onset and LP. Consistent with previous observations [21], we found a significant association between CSF levels of SNAP-25 at LP and survival, even after accounting for covariates such as codon 129 genotype, age at LP, and time between symptoms onset and LP.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, in line with recently proposed prognostic models [38,39], we carried out the survival analyses also considering clinical variables known to have a prognostic role in prion diseases such as age at LP, PRNP codon 129 genotype, and time between symptoms onset and LP. Consistent with previous observations [21], we found a significant association between CSF levels of SNAP-25 at LP and survival, even after accounting for covariates such as codon 129 genotype, age at LP, and time between symptoms onset and LP.…”
Section: Discussionmentioning
confidence: 99%
“…The median clinical duration is usually reported as five months with a range of only a few weeks to several years (2). Ability to estimate the likely clinical duration could help with timely decisions about care (8).…”
Section: Introductionmentioning
confidence: 99%
“…Human epidemiological and genetic studies have identified factors that associate with survival time in sCJD(2, 8, 18, 19), including demography, prion protein genotype, molecular strain typing of protease-resistant prion protein by Western blot analysis, and a range of biofluid, tissue, imaging, and neurophysiological biomarkers(20). Many biomarkers simply measure the rate or extent of neuronal injury, loss, or dysfunction, or immune cell or glial responses, whereas genetic associations are implicitly causal of modified clinical phenotypes.…”
Section: Introductionmentioning
confidence: 99%